Supply chain integration improvement action model for contractor in industrialised building systems (IBS) projects / Wan Zukri Wan Abdullah - Wan Abdullah, Wan Zukri (2023)
Supply Chain Integration (SCI) was the key to better construction project performance in improving the construction industry's performance to be more integrated. In accordance with National Construction Policy 2030 (NPC 2030), which has outlined some effective measures to improve the delivery system in addition to ensuring the success of public and private construction projects outlined which one of them is to increase awareness and campaign programs to enhance the understanding of quality assessment and utilisation of Industrialised Building System (IBS) technology in construction projects, especially to the Small and Medium Enterprises (SMEs). The Malaysian government has been persuaded to use the innovative approach of the Industrialised Building System (IBS) and Integrated Supply Chain to ensure the development of the construction industry in the right direction. It also found that the fragmentation and adversarial relationships among the stakeholder in the IBS supply chain has been identified as the main hindrance to the IBS construction project delivery. The difficulty in providing cooperation and integration among the IBS stakeholders needs to be addressed to ensure the delivery approach and arrangement in the procurement of current tasks can guarantee work continuity that can drive production excellence as a result of the effectiveness of the supply chain. The objectives of the research are to identify the major factors that affecting disintegration among the contractor that caused IBS construction projects delay; identify the most critical project phase that caused IBS project delay in proposing the completion time; examine the Key Performance Indicators (KPIs) towards successful IBS construction project; determine the Action taken by the contractor for each major factors to achieve the Key Performance Indicators (KPIs) and to develop the IBS SCI Improvement Action Model for contractor that related to KPIs towards successful IBS construction project. The research methodology is divided into 3 phases which are; 1) literature review, problem analysis and questionnaires design; 2) data collection, analysis and proposed Actual Conceptual SCI IBS Framework; and 3) develop the IBS SCI Improvement Model. Phase 1 started with the literature review, referring to a critical and systematic document containing the information required to obtain any relevant factors influencing the IBS Supply Chain Integration. Expert interviews and a pilot study were conducted for the questionnaire design. It aims at exploring and collecting data about a specific field of interest. In Phase 2, a set of questions was prepared to collect information for analysis in answering the research objectives. The data obtained from the main questionnaires were analysed using SPSS 28.0, including Cronbach's Alpha, factor analysis, the mean and standard deviation to achieve objectives one, two, three and four. Phase 2 ends with the analysis and report to propose the Actual SCI Conceptual Framework. In Phase 3, to achieve objective five, PLS-SEM 3.0 was used to evaluate the data, which consisted of two stages; evaluation of the measurement model and evaluation of the structural model to design the IBS SCI Improvement Action Model while also determining how the indicated variable (SCI factors and Action) relates to the KPIs. The model will contribute to a new guideline for the contractor to communicate for better supervision from the initial stage until the completion of the project. It will also provide information to project teams to perform various complementary tasks, visualization, construction and improving documentation accuracy.